THE EFFECT OF MARKETING MIX ON PURCHASING DECISION OF TUPPERWARE PRODUCTS AT SLD HUSNUL BAROKAH - Siahaan, Indri Oktaviani; Sembiring, Carolina F.; Hutajulu , Fharel M. (Fundamental Management Journal, 2022)
“The purpose of this research is to obtain information about the Influence, Price, Promotion and Distribution of Tupperware Product Purchase Decisions at SDL Husnul Barokah. The source of the data used is primary data obtained by distributing questionnaires to 50 respondents, while secondary data is obtained through library research from the Husnul Barokah SLD by searching the internet for data related to this research. The research method used in this research is quantitative analysis techniques. Meanwhile, in analyzing the data using SPSS 18. Testing the validity, reliability, classical assumptions, multiple linear regression, and hypotheses to test the data statistically. Through this research, it is known that the questionnaire is said to be valid because rcount > rtable, that is, each rcount score > 0.279. Likewise, the questionnaire data is also said to be reliable because the Cronbach Alpha is > 0.60. The conclusion in this study is that the product factor partially does not have a significant influence on the decision to buy Tupperware products at SDL Husnul Barokah. Meanwhile, price, promotion, and distribution partially have an influence on the decision to buy Tupperware at SDl Husnul Barokah. All variables simultaneously have a significant influence on purchasing decisions for Tupperware products at SDL Husnul Barokah.”Keywords: Product, Price, Promotion, Distribution, Product Purchase Decision